2014
DOI: 10.1186/s12974-014-0161-z
|View full text |Cite
|
Sign up to set email alerts
|

Microglia display modest phagocytic capacity for extracellular tau oligomers

Abstract: BackgroundAbnormal misfolded tau protein is a driving force of neurofibrillary degeneration in Alzheimer’s disease. It has been shown that tau oligomers play a crucial role in the formation of intracellular neurofibrillary tangles. They are intermediates between soluble tau monomers and insoluble tau filaments and are suspected contributors to disease pathogenesis. Oligomeric tau can be released into the extracellular space and spread throughout the brain. This finding opens the question of whether brain macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 80 publications
5
46
3
Order By: Relevance
“…Our results indicate that LPS increases N9 microglia phagocytosis, as previously described for LPS-treated BV2 cells, as well as primary cultures of microglia and macrophages [73]. In vivo studies showed that LPS administration increases microglia phagocytosis of viable neurons during development, inflammation, and neuropathology, a property denominated as phagoptosis [74].…”
Section: Discussionsupporting
confidence: 86%
“…Our results indicate that LPS increases N9 microglia phagocytosis, as previously described for LPS-treated BV2 cells, as well as primary cultures of microglia and macrophages [73]. In vivo studies showed that LPS administration increases microglia phagocytosis of viable neurons during development, inflammation, and neuropathology, a property denominated as phagoptosis [74].…”
Section: Discussionsupporting
confidence: 86%
“…A recent study reported that microglia display modest levels of phagocytic capacity for Tau oligomers that are increased by LPS activation (10). It is not clear how microglia might clear antibody-bound Tau.…”
mentioning
confidence: 99%
“…The most likely reason for the correlation observed between transcriptional changes in innate immune cells in blood and microglia in the CNS is that the inflammatory signals responsible for activating the microglial response are also present in blood. Inflammatory peptides are increased in the serum of AD patients [9], and there is evidence that monocytes are responsible for clearing circulating amyloid beta [35], tau [36], alpha-synuclein [37], and TDP-43 [38]. We saw no clear evidence of enrichment of neuron-, astrocyte-or oligodendrocyte-specific genes in any of the co-expression modules we identified in blood, which is unsurprising given that these other CNS cell types do not have analogous cell types in blood.…”
Section: Discussionmentioning
confidence: 99%